The use of nuclear weapons and human rights. (1st April 2016) - Casey-Maslen, Stuart
Abstract: International human rights law is an as-yet underused branch of international law when assessing the legality of nuclear weapons and advocating for their elimination. It offers a far greater range of implementation mechanisms than does international humanitarian law (IHL), and arguably strengthens the protections afforded to civilians and combatants under IHL, particularly in non-international armed conflict. Of particular relevance are the rights to life, to humane treatment, to health and to a healthy environment, associated with the right to a remedy for violations of any human rights.